Recent Advances in Hydrogel-Based Phototherapy for Tumor Treatment - Shuaiqi Gan; Yongzhi Wu; Xu Zhang; Zheng Zheng; Min Zhang; Li Long; Jinfeng Liao; Wenchuan Chen (Gels, 2023)
Phototherapeutic agent-based phototherapies activated by light have proven to be safe modalities for the treatment of various malignant tumor indications. The two main modalities of phototherapies include photothermal therapy, which causes localized thermal damage to target lesions, and photodynamic therapy, which causes localized chemical damage by generated reactive oxygen species (ROS). Conventional phototherapies suffer a major shortcoming in their clinical application due to their phototoxicity, which primarily arises from the uncontrolled distribution of phototherapeutic agents in vivo. For successful antitumor phototherapy, it is essential to ensure the generation of heat or ROS specifically occurs at the tumor site. To minimize the reverse side effects of phototherapy while improving its therapeutic performance, extensive research has focused on developing hydrogel-based phototherapy for tumor treatment. The utilization of hydrogels as drug carriers allows for the sustained delivery of phototherapeutic agents to tumor sites, thereby limiting their adverse effects. Herein, we summarize the recent advancements in the design of hydrogels for antitumor phototherapy, offer a comprehensive overview of the latest advances in hydrogel-based phototherapy and its combination with other therapeutic modalities for tumor treatment, and discuss the current clinical status of hydrogel-based antitumor phototherapy.